Plectocomia pierreana Becc. (Arecaceae Schutz-sch.) a new species for the flora of Vietnam - Phuong Anh, Tran Thi; Khoi, Nguyen Khac (Academia Journal of Biology, 2014)
The genus Plectocomia Mart. ex Blume had 16 species, distributed in India, Myanma, China, Laos, Cambodia, Thailand, Philippines and Vietnam. According to literatures there were 2 species in the flora of Vietnam, such as P. elongata Mart. ex Blume and P. khasyana Becc. & Hook.f. which was the synonym of P. kerrana Becc.. During the specimen study, we have found P. pierreana Becc. as a new record for the flora of Vietnam. This species was published by Gagnepain, 1937 in the “Flore GÐnÐrale de l’Indochine” as P. cambodiana Gagnep., and with the distribution in Cambodia. The specimens were collected in the Laocai, Tuyenquang and Vinhphuc provinces. This species differed from the others by group of sheath spines scattered, fruit 2 cm in diameter and bracts tomentosa.